Implementasi Pendidikan Multikultur di Sekolah Islam Indonesia dan Amerika - Husniya, Iftitahul (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
The implementation of multicultural education that respects equality in human life is one of the efforts in bridging and minimizing the tensions and friction that can cause conflict in a multicultural society. The results of this study reveal that the learning materials of Islamic Religious Education (PAI) in senior high school (SMA) contains multicultural values ​​such as democracy, tolerance and so forth. While the multicultural education in American Islamic schools makes students to be zealous to defend their own nation (America) and practice Islamic religion in earnest. In multicultural education, students are educated to have a paradigm that Islam is a religion that teaches kindness and tolerance, and is inclusive and ready to live side by side with different beliefs, as well as seeing differences as grace.